Analysis Of The National Health Insurance Program At Puskesmas Sempaja 2022 - Lisna Riana Ujuk; Nordianiwati (Universitas Widya Gama Mahakam Samarinda, 2022)
The data of JKN visitors to receive health services at Public Health Center (Puskesmas) 2021 every month in July was 12.910 people, August was 12.954 people, September was 12.986 people, and October was 12,603 people, and November was 12,907. The data on patient visits increased every month. This research used a type of case study research with a qualitative approach. Data collection techniques used interviews, documentation, and observation of 5 informants. Doctor, Head of Public Health Center, and JKN User. The data analysis technique used data collection, data reduction, data presentation, and conclusions. The results stated that there were still patients who did not know the service flow. The obstacles obtained at the Public Health Center were 3, namely the sudden request for a referral, patients still asking for a referral even though they could be treated at Puskesmas, and patients having difficulty following the requirements of JKN service recipients. The mobile JKN application has not been used very well by patients. It was concluded that there are patients who do not know the flow of services at the Puskesmas. The obstacle obtained is about referral services and mobile JKN, which is not yet known and appropriately utilized, so the usage is not optimal. Advice on the need to improve advanced technology services in public health center services and technology in patients and the need to educate patients about the service flow and referrals.